The fabrication of MEMS alkali metal vapor cells based on ultrafast laser welding for single beam magnetometer - Yanbin Wang; Mingzhi Yu; Yao Chen; Yintao Ma; Xiangguang Han; Yong Xia; Ju Guo; Ping Yang; Qijing Lin; Shujiang Ding; Libo Zhao (Microsystems & Nanoengineering)
Abstract The development of micro-electro-mechanical system (MEMS) alkali metal vapor cells offers the potential for the batch fabrication of micro-quantum sensors for atomic clocks, atomic magnetometers and atomic gyroscopes. The sealing of MEMS vapor cells is traditionally achieved by anodic bonding. However, high-temperature and high direct-voltage conditions during anodic bonding adversely affect the performance of the vapor cell. In this study, a fabrication method based on ultrafast laser welding integrated with a microfabrication process was developed for MEMS alkali metal vapor cells, and the energy-coupling mechanism of welding was analyzed. This method confined high temperatures to a localized area during laser welding. The cross-sections of the welding samples were analyzed, the element distribution was characterized, and the results showed that this method achieved high-strength sealing. Additionally, a platform for alkali metal injection and buffer gas charging was developed to enable the fabrication of MEMS vapor cells with ultrafast laser welding. The MEMS vapor cells were tested using absorption spectra, and the leakage rate under high-temperature vacuum conditions proved that high hermeticity could be achieved by ultrafast laser welding. Finally, MEMS vapor cells were used to fabricate a single-beam magnetometer, and its measurement sensitivity was determined experimentally. This process provides a new method for the efficient fabrication of MEMS vapor cells.